Ampliação de raio de pesquisa de triatomíneos na atividade de atendimento às notificações em área de Triatoma sordida (Stål, 1859) no Estado de São Paulo Broadening the scope of triatomine research in the attendance of notifications of Triatoma sordida (Stål, 1859) in the State of São Paulo - Rubens Antonio da Silva; Sirle Abdo Salloun Scandar; Clóvis Pauliquévis-Júnior; Susy Mary Perpétuo Sampaio; Vera Lúcia Cortiço Corrêa Rodrigues (Revista da Sociedade Brasileira de Medicina Tropical, 2005)
O objetivo deste estudo foi avaliar a ampliação da vistoria realizada nas unidades domiciliares situadas em um raio de 200m, a partir da casa notificante. Foram avaliadas as notificações recebidas pelos Serviços Regionais da Superintendência de Controle de Endemias de São José do Rio Preto, Araçatuba e Presidente Prudente, nos meses de agosto, setembro e outubro de 2002. Foram recebidas no período 263 notificações de triatomíneos, sendo 79 positivas. A ampliação de raio foi responsável pela pesquisa de mais 610 UD's, com presença de triatomíneos em 14,5% destas. Observou-se que 24,7% das UD's vizinhas a casa que notificou apresentou resultado positivo na pesquisa de triatomíneos. Quando a UD notificante apresentou resultado positivo na notificação, a ampliação de raio mostrou positividade em 42,5% das UD's obtendo-se valor de "Odds ratio" de 2,252 (1,25 The objective of this study was to broaden the inspection of home units to a radius of 200 meters from the residence of each notified case. The notifications received by the regional Services of SUCEN of São José do Rio Preto, Araçatuba and Presidente Prudente were evaluated in August, September and October of 2002. There was a total of 263 notifications of triatomines, of which 79 were positive. Broadening the scope meant another 610 domestic units were included in the investigation and in 14.5% of these triatomines were found. It was observed that 24.7% of the domestic units neighboring the house of the notified case presented positive results in the triatomines investigation. When a notified domestic unit presented a positive result, broadening the scope showed positivity in 42.5% of neighboring domestic units (Odds ratio 2.252 (1.25<OR<4.06, with a 95% confidence limit). This study demonstrated that it is necessary to broaden the scope of investigation when attending notifications by the local population.